La protección de los adultos en el derecho internacional privado codificado por la conferencia de La Haya: el convenio de 13 de enero de 2000 y sus soluciones = The protection of the adult in private international law codified by the Hague Conference : the Convention of 13 January 2000 and its solutions - Vicente Blanco, Dámaso-Javier (Oñati Socio-Legal Series, 2011)
The study aims to examine the fundamental character of the Convention of 13 January 2000 on the International Protection of Adults. The starting point is the need to respond by law to the new social realities created in market society. The study examines the characters and fundamental contents of the Convention: its origins and objectives, scope of the convention, jurisdiction of the authorities for the protection of the adult, the law applicable to measures of protection, the mandate in case of incapacity, as well as a reference to the recognition and enforcement and to the co-operation. The findings, highlights, by contrast, non-membership of the instrument to the trend of the current private international law of the European Union to the "reification" of international family relations.